Interference haptic stimulation and consistent quantitative tactility in transparent electrotactile screen with pressure-sensitive transistors - Lim, Kyeonghee; Lee, Jakyoung; Kim, Sumin; Oh, Myoungjae; Koh, Chin Su; Seo, Hunkyu; Hong, Yeon-Mi; Chung, Won Gi; Jang, Jiuk; Lim, Jung Ah; Jung, Hyun Ho; Park, Jang-Ung (Nature Publishing Group, 2024)
Integrating tactile feedback through haptic interfaces enhances experiences in virtual and augmented reality. However, electrotactile systems, which stimulate mechanoreceptors directly, often yield inconsistent tactile results due to variations in pressure between the device and the finger. In this study, we present the integration of a transparent electrotactile screen with pressure-sensitive transistors, ensuring highly consistent quantitative haptic sensations. These transistors effectively calibrate tactile variations caused by touch pressure. Additionally, we explore remote-distance tactile stimulations achieved through the interference of electromagnetic waves. We validated tactile perception using somatosensory evoked potentials, monitoring the somatosensory cortex response. Our haptic screen can stimulate diverse electrotactile sensations and demonstrate various tactile patterns, including Morse code and Braille, when integrated with portable smart devices, delivering a more immersive experience. Furthermore, interference of electric fields allows haptic stimulation to facilitate diverse stimulus positioning at lower current densities, extending the reach beyond direct contact with electrodes of our screen. Electrotactile systems can have inconsistent tactile results due to variations in pressure between the device and finger. Here, the authors report a transparent electrotactile device with pressure-sensitive transistors, enabling consistent electrotactility while interference stimulation maximizes the performance.